Reconstructing Thomist astrology: Robert Bellarmine and the papal bull Coeli et terrae. - Tarrant, Neil (Annals of Science, 2020)
Historians have portrayed the papal bull Coeli et terrae (1586) as a significant turning point in the history of the Catholic Church's censorship of astrology. They argue that this bull was intended to prohibit the idea that the stars could naturally incline humans towards future actions, but also had the effect of preventing the discussion of other forms of natural astrology including those useful to medicine, agriculture, and navigation. The bull, therefore, threatened to overturn principles established by Thomas Aquinas, which not only justified long-standing astrological practices, but also informed the Roman Inquisition's attitude towards this art. The promulgation of the bull has been attributed to the 'rigour' of the incumbent pope, Sixtus V. In this article I revise our understanding of this bull in two ways. First, I reconsider the Inquisition's attitude towards astrology in the mid-sixteenth century, arguing that its members promoted a limited form of Thomist astrology that did not permit the doctrine of inclination. Second, using Robert Bellarmine's unpublished lectures discussing Aquinas's views of astrology, I suggest that this attitude was common during the sixteenth century, and may have been caused by the crisis of Renaissance astrology precipitated by the work of Giovanni Pico.